Peran Komunikasi Verbal dan Nonverbal Dalam Dukungan Sosial Teman Sebaya Terhadap Resiliensi Mahasiswa - anhar, Anhar; Tasya, Tasya; Selviana, Selviana; Tanjung, Karina (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examines the role of verbal and non-verbal communication in peer social support and its impact on student resilience, an area that is still rarely studied. Academic and social challenges during lectures demand high resilience, and peer support is believed to strengthen this resilience. This study uses a quantitative approach and survey method, data from 15-20 students of various study programs at the Balikpapan College of Economics was collected through an online questionnaire covering aspects of demography, communication, and resilience. The analysis of the research data was carried out in a descriptive manner. The results showed that verbal communication, such as motivation, as well as non-verbal communication, such as eye contact, were significant in supporting resilience. The combination of these two forms of communication helps students cope with academic stress. These findings propose a communication-based mentoring program in educational institutions to improve student resilience and psychological well-being